Identification and Prioritization of Effective Factors on the Social Health of the Elderly Using DEMATEL and ISM Methods - Toktam Parvish; Hossein Behravan; Gholamreza Hasani Darmian (Gonabad University of Medical Sciences, 2021)
Background: The number of elderly people is growing continuously. These people are more vulnerable to social harm, such as loneliness, depression, etc, on the eve of aging. Therefore, it is important to promote their social health indicators as factors influencing social development. Generally, the interactions of various factors affect social health. Thus, this study aimed to identify, prioritize, and assess the extent of the interactions between the factors affecting the elderly's social health. Methods: The present study applied a combinatory research method, including two sections of qualitative and quantitative. In the qualitative section, factors that affected the elderly's social health were identified through the evaluation of 14 factors. In the quantitative section, the interpretive structural modeling and evaluation technique and decision-making test were used to evaluate factors and quantitatively analyze the relationships between factors, respectively. Besides, 12 experienced experts in the field of elderly health from the Deputy of Health of Khorasan Razavi province participated in this section. Results: The results showed that among the factors studied, socioeconomic status, social capital, residence (home shelter), social support, and environmental factors were effective factors on the social health of the elderly. Also, leisure time, lifestyle, and social vitality were identified as affected factors or effects. Conclusion: The researchers suggest that policymakers and specialists should consider prioritizing the causes and effects in the area of elderly's social health and pay particular attention and focus on the effective factors. Proper planning will create the ideal conditions for older people, reduce the economic burden of old age, and enhance social development and advancement in different fields.